(untitled) (Research in Agriculture Livestock and Fisheries, 2024)
The excessive use of fertilizers and pesticides in agriculture poses threats to ecosystems and human health. To mitigate these risks, researchers have turned their attention to pesticide-free production methods. This study aimed to assess the market opportunities for pesticide-free vegetables (PFVs) through determining consumers’ preferences and willingness to pay (WTP), along with identifying factors influencing consumers’ WTP decision in three major cities of the country, namely Dhaka, Khulna, and Mymensingh. Employing a multistage cluster sampling method, 150 samples were selected and data collection utilized the android-based app Kobo through direct interviews. The contingent valuation method (CVM) and double-bounded dichotomous choice model (DBDC) were used to estimate WTP and preferences while ordered logit model were employed to identify influencing factors. The findings indicated that over 90% of consumers in Mymensingh and over 92% in Dhaka and Khulna were willing to pay a premium for pesticide-free tomatoes and brinjal. Additionally, more than 18% and 19% of consumers expressed willingness to pay a 20% premium for brinjal and tomato, while over 39% were willing to pay for both a 10% premium. The study revealed that factors such as age, sex, education, household size, and income significantly influenced consumers’ WTP decisions, with age showing a negative correlation, while education and income were positively associated with interest in consuming pesticide-free vegetables. Overall, the study underscores the increasing demand for pesticide-free vegetables in urban areas, emphasizing the need for governments and stakeholders to develop supportive policies for sustainable market development. Res. Agric. Livest. Fish. Vol. 11, No. 1, April 2024: 69-77